Investigating different levels of salinity and drought stress on the germination and growth of Pennisetum divisum - fatemeh jamali; vahid Etemad (علوم و فناوری بذر ایران)
Research on the effect of salinity and drought stress on germination and growth pattern among pasture grass populations is very important to determine the potential of suitable species for restoration and protection as well as fodder production. For this purpose, a research was carried out to evaluate the salinity and drought stress of the Pennisetum divisum plant in the germination and seedling growth stage of 2019 in the seed laboratory of the Faculty of Agriculture of Tehran-Karaj University in the form of a completely randomized design and in 3 replications. The treatments of this experiment included 4 levels of salinity (100-150-200 and 300 mM sodium chloride), 4 levels of dryness (2-, 4-, 6- and 8-bar polyethylene glycol) and distilled water (control). The evaluated traits included germination percentage, germination speed, stem length and root length. The results showed that the germination percentage, germination speed, root length and shoot length increased with the increase of salinity stress up to 200 mM and then decreased so that practically no seeds germinated. In drought stress, the studied traits increased up to -6 times and then started to decrease. The results showed that the Pennisetum divisum plant is relatively resistant to salt and drought stress.